TMIC-62. INHIBITION OF TUMOR-ASSOCIATED COL1A1 MATRIX ARRESTS GLIOMA MESENCHYMAL TRANSFORMATION AND REPROGRAMS THE TUMOR MICROENVIRONMENT. (14th November 2022) - Comba, Andrea; Faisal, Syed M; Varela, Maria Luisa; Argento, Anna; Dunn, Patrick; Abel, Clifford; Hollon, Todd; Al-Holou, Wajd; Zamler, Daniel; Quass, Gunnar; Apostolides, Pierre; Kish, Phillip; et al.
Abstract: Tumor mesenchymal transformation (MT) is a hallmark of high-grade gliomas. The mesenchymal state is associated with specific changes related to cell adhesion, migration, and the extracellular matrix. Collagen 1a1 (COL1A1) is a main component of the extracellular matrix in gliomas, and its expression correlates inversely with patient survival. However, the cellular and molecular mechanisms of the tumor-associated COL1A1 matrix in gliomas remains elusive. Our study integrates histopathological features, spatially resolved transcriptomics, cellular dynamics and microenvironment alterations associated with MT in high-grade gliomas. Using deep learning analysis of mouse and human glioma histological samples we identified that the density of areas of MT, named oncostreams, correlates with tumor aggressiveness. Spatial transcriptomics analysis, using laser capture microdissection, identified a signature enriched in extracellular matrix related proteins, in which COL1A1 appeared as a key determinant of mesenchymal organization. Correspondingly, human and mouse high-grade gliomas showed prominent alignment of collagen fibers along these mesenchymal fascicles and higher COL1A1 expression compared to low-grade gliomas. Moreover, RNA fluorescent multiplex assays identified at single cell level that different cells within glioma tumors contribute to COL1A1 expression, including neoplastic cells and perivascular non-neoplastic cells such as ACTA2+, CYR61+ and FAP+. Inhibition of COL1A1 using genetically engineered mouse models decreased areas of mesenchymal transformation and increased survival. COL1A1 downregulation impaired tumor cell proliferation and remodeled the tumor microenvironment by reducing CD68+ macrophages/microglia cells, CD31+ endothelial cells, ACTA2+, CYR61+ and FAP+ perivascular cells, and increased GFAP+ astrocytes infiltration withing the tumor mass. Further studies, using ex-vivo glioma explants demonstrated that CO1A1 downregulation decreased collective invasion of the normal brain, supporting its importance in tumor progression. We propose that COL1A1 expression is a valuable marker for diagnosis, and COL1A1 depletion within glioma tumors is a promising direct or complementary therapeutic approach to reprogram mesenchymal transformation, and halt tumor growth.